Evan’s syndrome secondary to COVID-19 infection - Namala, Satya Prasad; Marimuthu, Aishwarya K.; Pandurangan, Prabu (International Journal of Research in Medical Sciences, 2022)
Wide range of autoimmune diseases are known to occur following SARS-CoV-2 infection. There are very few case reports of Evan’s syndrome secondary to COVID-19. We hereby report a case of Evan’s syndrome secondary to COVID-19 infection and discuss its management.